Saunders guide to success in nursing school 2017-2018 : - Stromberg, Holly (Elsevier, 2018)
The popular Saunders Guide to Success in Nursing School is a versatile organizational tool, a practical nursing orientation handbook, a clinical quick reference, and a resource directory all in one. This compact and affordable guide helps busy nursing students manage their time and perform to their fullest potential inside the classroom and during clincial rotations. The Guide not only provides time management and stress-reduction strategies, advise on study skills, and yearly, monthly, and weekly planners, but also comes equipped with a variety of helpful clincial tools like pain and neurological assessment scales, Joint Commission safety guidelines, information on common drug and lab values, and NCLEX preparation tips.